Meat, fat, and bone ratios of Icelandic lamb. Chemical composition of lamb meat and side products. - Hilmarsson, Óli Þór; Reykdal, Ólafur; Þorkelsson, Guðjón; Briem, Helgi; Halldórsson, Hafliði (Zenodo, 2024)
Meat, fat, and bone ratios of Icelandic lamb meat, were studied. Carcasses from the EUROP classes: O-2, R-2, R-3, U-2, U-3, U-3+, and E-3 were selected, nine carcasses from each class, a total of 63 carcasses. Carcasses from these classes represent 92% of the lamb meat production in Iceland as reported for 2021. Carcasses were selected during three slaughtering days, in two slaughterhouses in north and south Iceland. The EUROP classifications of carcasses were confirmed by a specialist from the Icelandic Food and Veterinary Authority. The carcasses were divided into halves the day after slaughtering. One half was divided into traditional cuts: leg, forequarter, saddle, and flank. The other half was used for study of various cuts, where each product was made from one of three selected carcass weight ranges: light carcasses below 14.5 kg, medium carcasses 14.5-16.8 kg and heavy carcasses 16.9-19.0 kg. Deboning was carried out on all products and yields were reported (meat, fat, bones, tendons). Wastage due to cutting, and deboning was reported. Tissue ratios for whole lamb carcasses were on average 59% meat, 16% fat, 18% bones, and 6% tendons. Wastage during cutting and deboning was 1,1%. The meat yields were highest for class U-2, except for forequarter which had a bit higher meat yield for class E-3. For conformation classes U and R, it was clear that fat yields were related to the definitions of fat thickness for fat classes 2, 3 and 3+. Yields were reported for meat, fat, bones, and tendons in 30 meat products. Highest meat yields were for leg products (74% and 69%). Selected nutrients were analysed in legs, forequarters, saddles, flanks, and several products. The results will be used for labelling and dissemination. Lamb meat was rich in vitamin B 12 , folate, potassium, and zinc. These nutrients can be used for nutrition declarations of the meat. The heavy metals mercury, cadmium, lead, and arsenic were below the quantification limits in lamb meat. The quantification limits were very low. Sampling of lamb ...